Regulating campaign finance and ensuring electoral fairness: An analysis of the Regulation of Election Expenditure Act No. 3 of 2023 of Sri Lanka - Susarithaa, S. (University of Colombo, 2025)
The elections in Sri Lanka have long been shaped by the influence of financial capital and campaign finance, particularly following the introduction of the Proportional Representation electoral system during the 1970s. The unregulated election campaign finance has impacted and undermined the electoral fairness and integrity of electoral competition in Sri Lanka. It allows wealth and money to play a dominant role in political competition. This paper examines the core research problem as the extent to which the Regulation of Election Expenditure Act No. 3 of 2023 can rectify financial disparities and inequality in election campaigns and enhance electoral fairness in Sri Lanka as an important statutory framework for regulating election campaign finance and expenditure. This paper examines the potential of this act to reduce the effects of financial disparities among candidates during the election campaign and provide an equitable opportunity to be elected to office. This study adopts a qualitative legal research methodology, relying on doctrinal analysis of the statute, relevant constitutional provisions, and secondary sources, including books, journal articles, and working papers. This study critically analyzes the potential of this legislative enactment in creating fair competition in elections. It also examines the problems associated with the enactment, specifically the effectiveness of the law, which is hindered by ambiguous provisions, limited enforcement power vested in the Election Commission, and a lack of oversight mechanisms...
Keywords: Electoral fairness; Campaign finance; Election expenditure; Representative democracy; Accountability